2015
DOI: 10.1111/jfbc.12110
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Free Radical-Scavenging Potential of Essential Oil from E nteromorpha linza  L. Prepared by Microwave-Assisted Hydrodistillation

Abstract: The seaweed Enteromorpha linza has long been used as a food source rich in natural bioactive compounds in various regions of the world. In the present study, the essential oil from E. linza, extracted by microwave-assisted hydrodistillation, was analyzed for its chemical composition and was evaluated for its free radicalscavenging and antioxidant potential. Gas chromatography and mass spectroscopy revealed the presence of 24 compounds in the seaweed essential oil (SEO), among which hexadecanoic acid (47.32%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 44 publications
(62 reference statements)
0
27
0
Order By: Relevance
“…The DPPH free radical scavenging potential of AgNPs was determined as previously described ( Patra et al, 2015 ). Briefly, five different concentrations (20–100 μg/mL) of AgNPs and ascorbic acid (ASA) as the standard reference compound was assayed.…”
Section: Methodsmentioning
confidence: 99%
“…The DPPH free radical scavenging potential of AgNPs was determined as previously described ( Patra et al, 2015 ). Briefly, five different concentrations (20–100 μg/mL) of AgNPs and ascorbic acid (ASA) as the standard reference compound was assayed.…”
Section: Methodsmentioning
confidence: 99%
“…The intensification of the extraction stage can reduce the time and energy demand. Patra et al [ 120 ] proposed microwave-assisted hydrodistillation to extract the essential oil from Enteromorpha linza . The major active compounds, such as n -hexanal, 2-chloro-5-methyl-4-(2-thienyl) pyrimidine, tetradecanoic acid, pentadecanoic acid, ( z , z )-6,9- cis -3,4-epoxy-nonadecadiene, 13-octadecenal and azetidine, individually or synergistically inhibited the growth of pathogenic bacteria.…”
Section: Production Of Antimicrobials From Seaweedmentioning
confidence: 99%
“…Tonones are a series of closely related chemical substances that are part of a group of compounds known as rose ketones, which are also as potent odor‐active compounds of several types of fruits. β ‐Ionone is a significant contributor to the aroma of roses, despite its relatively low concentration, is an important fragrance chemical used in perfumery, and exhibits pronounced biological activities . Despite the structural novelty and attractive biological activities of the ionones, a close look into the literature revealed that the ionone ‐ incorporated scaffolds have not yet been widely studied.…”
Section: Introductionmentioning
confidence: 99%